Pengaruh Konsentrasi Ekstrak Etanol Rimpang Jahe Merah (Zingiber Officinale Rosc) Terhadap Kematian Larva Nyamuk Aedes Aegypti - Suadnyani, A.A Indah; Sudarmaja, I Made (E-Jurnal Medika Udayana; Vol 6 No 11 (2017): E-Jurnal Medika Udayana, 2017)
Aedes aegypti is one of the vectors of disease transmission Dengue Hemorrhagic Fever (DHF). The observation of the Ministry of Health in 2016, extraordinary events (KLB) DHF were reported in 9 districts and 2 cities of seven provinces, including the city of Denpasar and Gianyar Regency. Indonesia has a lot of plants containing insecticidal compounds one of which is a red ginger plant (Zingiber officinale Rosc.). Compound essential oils and flavonoids contained in red ginger allegedly capable as natural biolarvasida. The aim of studies to determine the effect of red ginger ethanol extract concentration to mortality of Aedes aegypti larvae. The study design is a randomized experimental purely with post test only control group design with 6 treatments and 5 replications. The concentration of ethanol extract of red ginger used is 1%, 1.5%, 2%, 2.5%, 3% and 0% as a negative control. The sample used was the third instar larvae of Aedes aegypti as many as 150 animals. The results obtained, concentrations of 3% were able to kill the larvae of Aedes aegypti at most at 96% with a 45-minute observation time. One Way Anova test results obtained p value = 0.000 (p <0.05), which means there is a statistically significant difference against Aedes aegypti larvae mortality between the groups studied concentration. Post Hoc Analysis of obtained results, there are significant differences between concentrations of 0% and 1.5%, 0% and 2%, 0% and 2.5%, 0% and 3%, 1% and 3%. The ethanol extract of red ginger is effective in killing mosquito larvae of Aedes aegypti compared with controls. Keyword : Red ginger, Effect Concentration, Dengue Hemorrhagic Fever